2001
DOI: 10.1128/jb.183.22.6714-6716.2001
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Prokaryotic and Eukaryotic Species in All Subgroups of the PP i -Dependent Group II Phosphofructokinase Protein Family

Abstract: Inorganic pyrophosphate-dependent phosphofructokinase (PP i -PFK) of the amitochondriate eukaryote Mastigamoeba balamuthi was sequenced and showed about 60% identity to PP i -PFKs from two eubacteria, Propionibacterium freudenreichii and Sinorhizobium meliloti. These gene products represent a newly recognized lineage of PFKs. All four lineages of group II PFKs, as defined by phylogenetic analysis, contained both prokaryotic and eukaryotic species, underlining the complex evolutionary history of this enzyme.We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Even here, however, specialized biochemical twists maximize the ATP yield from what could be considered an inefficient catabolism of fuel sources. For instance, in glycolysis, which provides the major energy generating pathway, the phosphofructokinase from several enteric (intestinal) parasites is pyrophosphate (PP i ) rather than ATP dependent (Denton et al 1996;Muller et al 2001). In Giardia, E. histolytica, and probably Cryptosporidium too, the glycolytic end-product, pyruvate, can be metabolized to acetyl-CoA, which is then the substrate for acetyl-CoA synthetase.…”
Section: Comparative Metabolism: Survival Within a Nichementioning
confidence: 99%
“…Even here, however, specialized biochemical twists maximize the ATP yield from what could be considered an inefficient catabolism of fuel sources. For instance, in glycolysis, which provides the major energy generating pathway, the phosphofructokinase from several enteric (intestinal) parasites is pyrophosphate (PP i ) rather than ATP dependent (Denton et al 1996;Muller et al 2001). In Giardia, E. histolytica, and probably Cryptosporidium too, the glycolytic end-product, pyruvate, can be metabolized to acetyl-CoA, which is then the substrate for acetyl-CoA synthetase.…”
Section: Comparative Metabolism: Survival Within a Nichementioning
confidence: 99%
“…Amino acids essential for ATP-PFK and PPi-phosphofructokinase (PFP) at 104 and 124 position [120]. Several duplication and HGT fl ux the phylogeny of PFK [121]. Conservation Aquifex aeolicus and Thermotoga maritima Large number of genes that are most similar in their protein [117] Archaeoglobus fulgidus Fatty acid metabolism; Tryptophan biosynthesis pathway closely related to eubacterium Bacillus subtilis [73,117] Bacillus subtilis and B. halodurans Prophage like regions [117] Bacteria and fungi ß-glucuronidase (gus) genes [159] Bacteria and archaea FtsZ, a cell division protein [160,161] Bacteria and rumen Ciliates Expressed genes [162] Chlamydia trachomatis Polymorphic membrane protein C gene [163] Clostridium acetobutylicum 3-Isopropylmalate dehydratase, small subunit 3-Isopropylmalate dehydratase, large subunit 2-Isopropylmalate synthase [164] Cyanobacteria and α-proteobacteria (Rickettsia and Ehrlichia) are nearest to chloroplast and mitochondria HSP60, a major bacterial antigenic protein [165,166] Cyanobacteria and γ-proteobacteria ArsC gene (arsenate reductase) [167] Cyanobacteria and chloroplast genome of Euglena myxocylindracea psbA intron [168] Deinococcus radiodurans dTDP-4-dehydrorhamnose epimerase (Lipopolysaccharide biosynthesis) [118,164] …”
Section: Transcription and Regulatory Activitiesmentioning
confidence: 99%
“…A cytoplasmic isoenzyme of unclear function also exists in C3 and C4 plants, and it has been suggested that it may have a glycolytic role, especially in oxygen-starved tissues (22). Trypanosomatids target PPDK to glycosomes where it fulfills a thermodynamic role of pyrophosphate recycling in place of pyrophosphatase (1).At present, studies on the molecular evolution of PP i -linked glycolysis have focused almost exclusively on PFK and PFP (3,27). These proteins are homologous, and the gene family has had a complex evolutionary history including multiple events of duplication, loss, and lateral gene transfer (3,27).…”
mentioning
confidence: 99%
“…At present, studies on the molecular evolution of PP i -linked glycolysis have focused almost exclusively on PFK and PFP (3,27). These proteins are homologous, and the gene family has had a complex evolutionary history including multiple events of duplication, loss, and lateral gene transfer (3,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation